Surface and Catalytic Properties of NiO and CoO Solids Doped with Cobalt and Nickel Ions - G.A. El-Shobaky; A.M. Turky; A.M. Ghozza (Adsorption Science & Technology)
The effects of doping NiO and Co 3 O 4 solids with cobalt and nickel species on their surface and catalytic properties were investigated. The amounts of dopant, in the form of the corresponding nitrate, were varied between 0.5–6.0 mol% cobalt ions and 2.0–6.0 mol% nickel ions. Pure and variously doped solids were subjected to thermal treatment at 300–700°C. The techniques employed were XRD, nitrogen adsorption at −196°C, decomposition of H 2 O 2 at 30–50°C and estimation of the amount of surface excess oxygen on the variously prepared solids as determined by the hydrazine method. The results obtained revealed that the pure and variously doped NiO samples precalcined at 300°C consisted of a finely divided NiO phase having an average particle size of ca. 40 Å. Pure and variously doped Co 3 O 4 specimens preheated at 500°C and 700°C were composed of a Co 3 O 4 phase with a much bigger particle size (230 Å and 350 Å, respectively, for the solids precalcined at 500°C and 700°C). Doping of NiO followed by thermal treatment at 300°C and 500°C resulted in a measurable decrease in its BET surface area (19–23%), while doping of Co 3 O 4 with nickel species followed by heating at 500°C and 700°C brought about a significant increase in its specific surface area (56–60%). Doping each of the NiO and Co 3 O 4 solids with cobalt and nickel species greatly increased the amount of surface excess oxygen and effected a considerable increase in their catalytic activities. This increase was, however, much more pronounced in the case of NiO which attained a value of ca. 100-fold. Doping of NiO with cobalt species followed by thermal treatment at 300°C and 500°C decreased the activation energy (DE) of the catalyzed reaction to an extent proportional to the amount of dopant added. On the other hand, doping of Co 3 O 4 with nickel species followed by thermal treatment at 500°C and 700°C did not change the value of DE. These results suggest that doping of Co 3 O 4 with nickel species did not modify the mechanism of the catalyzed reaction but increased the concentration of catalytically active sites without changing their energetic nature.